SIKAP APRESIASI KREATIF SISWA DALAM MEMPELAJARI KARYA SASTRA UNTUK MENINGKATKAN RESPONS KEJIWAAN SISWA TERHADAP KARYA SASTRA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IVA SDN 144 PEKANBARU - Chamsriana Chamsriana (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
This study aims to look at the attitude of creative appreciation of students in studying literature to improve students' psychiatric responses to literature in Indonesian students. The design of this study is classroom action research with three cycles. The research subjects are fourth grade students with a total of 25 people. The results showed the attitude of students' creative appreciation in interpreting behavior, the nature of sensitivity and capturing ideas of literary works can be raised in students slowly during the learning process and increase every cycle. Then the students' psychological responses in interpreting behavior, the nature of sensitivity and capturing ideas of literary work can motivate students both internally and externally so that results are improved.